The stability of big-five personality traits - Deborah A. Cobb-Clark; Stefanie Schurer (Institute for the Study of Labor (IZA), 2011)
We use a large, nationally-representative sample of working-age adults to demonstrate that personality (as measured by the Big Five) is stable over a four-year period. Average personality changes are small and do not vary substantially across age groups. Intra-individual personality change is generally unrelated to experiencing adverse life events and is unlikely to be economically meaningful. Like other non-cognitive traits, personality can be modeled as a stable input into many economic decisions.
urn:nbn:de:101:1-201109288861
Keywords: J24; C18; 330; non-cognitive skills; Big-Five personality traits; stability; Kognition; Qualifikation; Persönlichkeitspsychologie